PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPMd) DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Hutabarat, Raisa Betsaida; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
PNPM Rural powerty is a program that has been implemented since 2007. Implementation of the National Program for Community Empowerment in Rural Areas village District has been done since 1998. Issues raised is how the National Programme Implementation of the National Program for Community Empowerment in Rural Areas in Village District of Siak Hulu Regency of Kamparin 2015 based on the timeliness and accuracy of the cos. This research aims to identity and analysis the implementation of the National Program for Community Empowerment in Rural Areas in Village District of Siak Hulu Regency of Kampar. This is adescriptive qualitative study which gives a clear and detailed illustration based on the facts was found in the observation.Theory used in this study principles of management from Teryy in Manullang (2012:8) and teory empowerment by Mardikanto dan Soebiato(2015:126) interpretes the factors that affect one is success or failure in the implementation of the National Program Community Empowerment in Rural Areas Village District of Siak Hulu Regency of Kampar in the collections data use observation and interview technigue kualitative. Technique analysis is descriptive qualitative.After research had been done we found that implementation of the National Program for Community Empowerment in Rural Areas In Village District of Siak Hulu Regency of Kampar well and eased the burden Siak Hulu district every year. Also there are problem are face in running the implementation of the National Program for Community Empowerment in Rural Areas that are human resourches lack of public awareness and undiscipline of time in practice it.Keyword: The Implementation, National program for Community Empowerment in Rural Areas.